Modeling the Mechanical Behavior of Dynamically Deformed Cu using the Theories of Crystal Plasticity. (2017) - Chandra, Sagar; Samal, M.K.; Chavan, V.M.; Patel, R.J.
Abstract: A phenomenological constitutive model for polycrystalline plasticity is evaluated by comparing the predictions for the evolution of deformation response of the material under dynamic compression. Copper (Cu) is selected as the model material. The mechanical response of dynamically deformed single crystal and polycrystalline Cu is simulated in the framework of finite element method. The results are in good agreement with the experiments in terms of stress-strain curves and shape changes albeit with different parameter sets for single crystal and polycrystal Cu. This is suggestive of the key role of other microstructural features like grain boundaries (absent in single crystals) in governing plasticity in polycrystalline materials.